Multidisciplinary Management of Adult Orbital Rhabdomyosarcoma*. (June 2013) - Bagdonaite, Laura; Jeeva, Irfan; Chang, Bernard Y. P.; Kalantzis, George; El-Hindy, Nabil
ABSTRACT We report the case of a 52-year-old man who presented with a 10-day history of right eye and eyelid inflammation and intermittent diplopia following blunt trauma to the right eyebrow. The CT and MRI scans revealed an extraconal soft tissue mass on the orbital floor with maxillary and ethmoid sinus wall destruction, which on orbital biopsy was proven to be an Alveolar Rhabdomyosarcoma. The patient had a central retinal vein occlusion due to mass effect that resulted in total visual loss at 2 months. He was referred to oncologists who treated him according to the paediatric RMS protocol and is still in remission at 2-year follow-up. Rhabdomyosarcoma is a rare tumour in adults which requires multi-disciplinary management. This highlights the necessity of considering rhabdomyosarcoma in the differential diagnosis of orbital tumours in any age group.